PEMBERDAYAAN PEMUDA DALAM PELAKSANAAN PPKM MANDIRI DI DESA WIROGUNAN PADA MASA PANDEMI COVID – 19 - Ika Murtiningsih; Suyahman; Vinsensius Singgih; Wahyu Putri Hasanah (Institut Agama Islam Ngawi, 2022)
Abstract Youth empowerment aims to increase the role of youth in tackling and reducing the percentage of covid-19 cases through social activities that can help residents who are confirmed to be covid-19. The service activity was carried out in Wirogunan Village, Kartasura District, Sukoharjo Regency. The method used in Community Service with the theme of youth empowerment is mentoring with a Participatory Rural Appraisal (PRA) approach, which is an approach in formulating plans and policies in rural areas by involving youth as effectively as possible. Mentoring activities were carried out for 3 weeks with 5 people from Toughness Youth. The results of the implementation, namely the overall empowerment of youth in the implementation of independent PPKM in Wirogunan village during the covid-19 pandemic can be said to be successful, because there is an increase in knowledge and skills as well as a conscious and caring attitude towards improving the welfare of the affected residents. The results of the pre test stated that the knowledge, skills and attitudes of youth regarding youth empowerment in the implementation of independent PPKM in Wirogunan village during the covid-19 pandemic was 30%. While the results after the post test and mentoring were carried out, the knowledge and skills and attitudes of conscious and caring behavior of youth increased to 90%. This success can be measured by the number of youths who play an active role in these “Toughness Youth” activities, and can also be seen from the satisfaction of the youth after participating in the activities, thus motivating youth to improve the welfare of the residents in Wirogunan Village, Kartasura District, Sukoharjo Regency. Keywords: Empowerment, Youth, Pandemic